Accountability and transparency as learning processes in private, public and global governance - Rodolfo Apreda (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2014)
This paper argues that accountability in organizations should not be constrained to responsibilities alone, but it must also comprise the previous commitments without which responsibilities remain meaningless. It also asserts that transparency should not be merely predicated upon the production of information but be focused instead on stakeholders who lay claim to their essential rights of being informed. Afterwards, it deals with a learning-process approach that brings to light the prime linkage between accountability and transparency in the building of private, public and global governance.
Keywords: G34; G38; F65; H83; 330; accountability; transparency; learning processes; governance; commitments; responsibilities